Peran Growth Opportunities, Free Cash Flow, dan Relative Issue Size dalam Reaksi Pasar terhadap Pengumuman Right Issue - Synthia Atas Sari; Hartiwi Prabowo (The Winners, 2007)
Right issue is when a firm announces its plan to publicly offer additional shares of common stock after Initial Public Offering (IPO). The aim of this research are to test market stock price and examine the role of growth opportunities in stock price reaction to right issue announcement. Sample was taking from companies which been listed in Jakarta Stock Exchange and publish right issue from 1998 to 2005. To measure growth opportunities, the companies were divided into 2 groups, growth and mature. This classification using Tobin’s q proxy method (market-book value ratio). The research have final conclusion, that is at right issue announcement in Jakarta Stock Exchange, market give positive reaction and statistically significant, and so in normal period.